Changes in activity, structure and morphology of horseradish peroxidase induced by cold plasma. (15th December 2019) - Han, Yong-Xu; Cheng, Jun-Hu; Sun, Da-Wen
Highlights: Horseradish peroxidase was inhibited by atmospheric-pressure plasma jet. Plasma species changed the secondary and tertiary structures of peroxidase. Degradation of heme active sites existed in peroxidase was shown. Aggregation and disaggregation of peroxidase molecules were observed. The mechanism of plasma active species interacting with peroxidase was explored. Abstract: Cold plasma is an emerging technology increasingly applied in the agri-food industry. For fruit and vegetables, enzymatic browning is a common phenomenon, causing quality deterioration. The objective of this study was to illustrate the effect of microscale atmospheric-pressure plasma jet (µAPPJ) plasma on the horseradish peroxidase (HRP). Results showed that after plasma treatment for 10 min, the residual activity of HRP was decreased to around 17%, and modification of secondary and tertiary structures were confirmed. The atomic force microscope (AFM) analysis revealed that the aggregation of enzyme protein was enhanced with prolonging treatment time. It was concluded that the activity of HRP could be reduced with destruction of structures and deformation of microstructure induced by µAPPJ plasma. The current study attempted to provide new idea for inhibiting browning enzymes of fruit and vegetables with plasma technology through deeper understanding of the interaction mechanism of plasma active species with enzymes.